«¡España viva!»: Personifications of Spain in Lope de Vega's 'comedias de santos' - Norton, R (Universitat Autònoma de Barcelona - Revistes Digitals, 2016)
The frequent deployment of non-human characters is a distinctive feature of Golden-Age hagiographic drama. Non-human characters intervene in every one of the twenty-five comedias by Lope de Vega that can, according to the criteria applied by Robert Morrison [2000:97], legitimately be considered saints plays. Lope’s non-human characters can be divided into three broad categories, although there can be some overlap.